2022
DOI: 10.1002/adfm.202111529
|View full text |Cite
|
Sign up to set email alerts
|

One‐Interlayer‐Twisted Multilayer MoS2 Moiré Superlattices

Abstract: Twist angle provides a new degree of freedom for 2D material modifications. In principle, the intrinsic properties of twisted multilayers can be regulated by twist angle between each adjacent layer and thus have greater tunability than widely studied bilayer structures. Considering its complexity, it is important to first investigate the simplest twisted multilayers with only one interface twisted. In this work, multilayer Moiré superlattices with only one twisted interface via paraffin‐assisted folding of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 58 publications
1
26
1
Order By: Relevance
“…Theoretical studies have revealed fascinating physical properties in continuously twisted multilayer systems, forming the basis for “3D twistronics”; , for example, quantum geometry has been predicted to govern superconductivity and superfluidity in platforms including, but not limited to, twisted multilayer graphene . However, the “tear-and-stack” technique, the most prevalent way to fabricate twisted 2D structures, has limited capability and throughput for creating 3D twistronics. , In light of this limitation, direct synthesis of continuously twisted TMD structures, termed “supertwisted spirals”, has been achieved via screw dislocation driven growth on non-Euclidean surfaces …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies have revealed fascinating physical properties in continuously twisted multilayer systems, forming the basis for “3D twistronics”; , for example, quantum geometry has been predicted to govern superconductivity and superfluidity in platforms including, but not limited to, twisted multilayer graphene . However, the “tear-and-stack” technique, the most prevalent way to fabricate twisted 2D structures, has limited capability and throughput for creating 3D twistronics. , In light of this limitation, direct synthesis of continuously twisted TMD structures, termed “supertwisted spirals”, has been achieved via screw dislocation driven growth on non-Euclidean surfaces …”
mentioning
confidence: 99%
“…10 However, the "tearand-stack" technique, the most prevalent way to fabricate twisted 2D structures, has limited capability and throughput for creating 3D twistronics. 20,21 In light of this limitation, direct synthesis of continuously twisted TMD structures, termed "supertwisted spirals", has been achieved via screw dislocation driven growth on non-Euclidean surfaces. 11 The presence of screw dislocations and curved substrates disrupts the perfect crystalline periodicity, thereby inducing a native strain field in supertwisted spirals.…”
mentioning
confidence: 99%
“…Artificial stacking has been used extensively in constructing twist multilayer systems, but the transfer process is complicated, and it is not suitable for the systematic study of the twist angle-related characteristics of 2DMs . The emerging paraffin-assisted folding strategy on untwisted stacked multilayers of MoS 2 can construct a multilayer interlayer structure with only one twisted lattice interface, but it is time-consuming. , Thus, it is of great importance to obtain twisted multilayer MoS 2 in a stable and easy-to-fabricate method.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, with enormous amounts of possible combinations of twist angles at different layer interfaces, the investigation of the twisted multilayer is much more complicated than that of the twisted bilayer. Therefore, it is necessary to fabricate multilayer structures that contain one-interlayer-twisted to understand the effects of twisted multilayer systems . Artificial stacking has been used extensively in constructing twist multilayer systems, but the transfer process is complicated, and it is not suitable for the systematic study of the twist angle-related characteristics of 2DMs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation